2021
DOI: 10.3389/fnins.2021.799916
|View full text |Cite
|
Sign up to set email alerts
|

Altered Static and Dynamic Interhemispheric Resting-State Functional Connectivity in Patients With Thyroid-Associated Ophthalmopathy

Abstract: Purpose: Thyroid-associated ophthalmopathy (TAO) is a debilitating and sight-threatening autoimmune disease that severely impairs patients’ quality of life. Besides the most common ophthalmic manifestations, the emotional and psychiatric disturbances are also usually observed in clinical settings. This study was to investigate the interhemispheric functional connectivity alterations in TAO patients using resting-state functional magnetic resonance imaging (rs-fMRI).Methods: Twenty-eight TAO patients and 22 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…The decreased dFC between these two brain regions would be an indicator that the functional transmission of the dorsal visual stream might be disrupted in TAO. In addition, abnormalities in dorsal visual stream have also been reported in previous rs‐fMRI studies of TAO (Chen, Hu, Wu, Chen, Zhou, Chen, Xu, & Wu, 2021 ; Jiang et al, 2022 ), which further confirmed our hypothesis. Interestingly, the STG and TPOsup of TAO in our dALFF results showed higher temporal variability of brain activity.…”
Section: Discussionsupporting
confidence: 91%
“…The decreased dFC between these two brain regions would be an indicator that the functional transmission of the dorsal visual stream might be disrupted in TAO. In addition, abnormalities in dorsal visual stream have also been reported in previous rs‐fMRI studies of TAO (Chen, Hu, Wu, Chen, Zhou, Chen, Xu, & Wu, 2021 ; Jiang et al, 2022 ), which further confirmed our hypothesis. Interestingly, the STG and TPOsup of TAO in our dALFF results showed higher temporal variability of brain activity.…”
Section: Discussionsupporting
confidence: 91%
“…Functional connectivity belongs to a useful measurement reflecting changes of brain functional integration ( 14 ), while it was seldom focused in studies on TAO. Until now, only one study reported the interhemispheric functional connectivity alterations of TAO using voxel-mirrored homotopic connectivity ( 15 ). However, it ignored the interregional and intraregional functional interactions of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…found that the changes of gray matter volume in PCU were associated with affective and cognitive dysfunctions in active TAO ( 36 ). Decreased voxel-mirrored homotopic connectivity of PCU was also found in TAO in a resting-state functional MRI study ( 10 ). CUN is a wedge-shaped area of the occipital lobe, which is well known as an important part of visual path.…”
Section: Discussionmentioning
confidence: 91%
“…The significance of classification accuracy was validated using a non-parametric permutation test with 5000 permutations. All detailed steps of SVM analysis could be referred to a previous study ( 10 ).…”
Section: Methodsmentioning
confidence: 99%